Historical and future storm surge around New Zealand: From the 19th century to the end of the 21st century. (2nd September 2019) - Cagigal, Laura; Rueda, Ana; Castanedo, Sonia; Cid, Alba; Perez, Jorge; Stephens, Scott A.; Coco, Giovanni; Méndez, Fernando J.
Abstract: We developed a new hindcast for storm surge at a 0.25° spatial scale for the whole New Zealand area using a statistical downscaling technique that links the mean local atmospheric conditions with the maximum storm surge levels at a daily scale. After validating the hindcast against sea level instrumental records from 17 tidal gauges around New Zealand, the same technique has been applied to obtain storm surge projections until 2, 100 using different global climate models. The global climate models have been previously classified according to their ability to reproduce the past climatology in the studied area and seven models have been selected in order to explore their effect on storm surge projections. For the two representative Concentration Pathways studied, the projections indicate that the storm surge associated with the 50 years return period will increase in magnitude in the Southern areas while it will decrease in the Northern region. Even where a decreasing linear trend over the annual maxima is observed in the future time series, sporadic events of higher magnitude than the historical peaks can be. Abstract : We present a general methodology based on statistical downscaling and weather types to obtain hindcasts of storm surge from the 19th century, and to develop storm surge projections from present until the end of the 21st century under different climate change scenarios. The methodology has been successfully applied to the New Zealand area at a 0.25° resolution and it is envisaged to be critical for coastal management and planning as estimation of storm surge can be of primary importance for the estimation of coastal hazards.